Katalogisasi Naskah Kuno Sebagai Pelestarian Informasi Naskah: Analisis Systematic Literature Review - Nur Aisyah, Sofia; Lawanda, Ike Iswary (Perpustakaan Nasional, 2024)
There is a need to preserve manuscript information in an effort to save it, one of which is cataloging, which will make it easier for users to access manuscript searches. This article will discuss the techniques used in the process of cataloging ancient manuscripts, the contributions made to the cataloging of ancient manuscripts, and the challenges faced in the process of cataloging ancient manuscripts for the preservation of their information. The method used in this research is a systematic literature review (SLR) using publication citation limits from the period 2018–2023, or the last 6 years. The results show that various cataloging techniques rely on descriptive information from manuscripts to identify ancient manuscripts with diverse languages and characters. Apart from that, the use of bibliographic records and comparing standards to adjust the condition of manuscripts is also used in manuscript cataloging techniques. The contribution of cataloging ancient manuscripts has influenced aspects such as inaccuracies, digitization, software development, and standardization. Challenges in cataloging ancient manuscripts include technical issues such as inaccuracies and mistrust, as well as operational challenges due to limited resources and funding.